Development and characterization of microsatellite loci for Campomanesia xanthocarpa (Myrtaceae) and cross amplification in related species - Bruna Delgado Góes; Eduardo Augusto Ruas; Lucas Milanez Benício; Daniele Cassiano; Felipe Pinheiro de Souza; Paulo Maurício Ruas (Acta Scientiarum. Biological Sciences, 2019)
Campomanesia xanthocarpa is a native tree, of common occurrence in almost all Brazilian Forest formations, which has its fruits and timber with high commercial value. Using an enriched genomic library we isolated and characterized microsatellite loci for C. xanthocarpa (Myrtaceae), in order to estimate genetic diversity parameters for this and related species. Twenty-eight microsatellite loci were identified and ten of them successfully amplified and showed polymorphism in a sample of 96 individuals, from four natural populations. The number of alleles per locus ranged from two to eight, and the observed and expected heterozygosities varied from 0.042 to 1.000 and from 0.294 to 0.855, respectively. These markers were tested and validated in two related species (C. eugenioides and C. guazumifolia). The microsatellite markers will be used in further studies of population genetics of C. xanthocarpa, in order to understand the genetic variability and to define the strategies needed for the conservation of the species.